Offering our gifts, partnering for change: decolonizing experimentation in Winnipeg-based settler archives - Story, Sarah (2017)
Since the nineteen-fifties, Indigenous residents of Winnipeg, Manitoba have conceptualized and developed distinct strategies in response to the impacts of settler colonialism. Roughly seventy organizations have been established by and for Indigenous peoples, including the first Indian and Metis Friendship Centre in Canada, the largest non-mandated family resource centre in the Province of Manitoba, a worker’s food cooperative, housing corporation, political organizations, and many other community initiatives. Until recently, Winnipeg-based archives have overlooked this aspect of the city’s history. This thesis closely examines the collaborative efforts of “Preserving the History of Urban Aboriginal Institutional Development in Winnipeg”. This project was the first active attempt to centralize and archive the documentary history of contemporary Indigenous experiences in Winnipeg. The project revealed a number of challenges with transferring Indigenous records out of the rooted context of the community into an institutional archive. It demonstrated need for Winnipeg-based archivists and Indigenous group’s experienced in decolonizing practice to work together to create culturally safe repositories and ensure future archives reflective of urban Indigenous identity, memory, and experience. This thesis responds to recent calls to decolonize settler archives by advancing the idea of policy change in institutional archives based on local notions of urban Indigenous knowledge stewardship. More specifically, this study argues that centering local Indigenous ways of conceptualizing, keeping and sharing information and knowledge is vital to genuine archival decolonization efforts. In conclusion, this thesis advocates local experimentation and collaboration to generate culturally safe repositories, as well as the redistribution of skills, resources and funding to support local Indigenous archives development in Treaty Number One to support Indigenous-driven efforts to rebuild community and reclaim Indigenous sovereignty over ...